Pengembangan Sistem Informasi Manajemen Laboratorium Berbasis Web pada Jurusan Teknik Elektro Politeknik Negeri Banjarmasin - Puspa Ayu Yohana; Herri Apriana (LPPM Politeknik Jambi, 2019)
The Laboratory of the Electrical Engineering Department is one of the important tools to help practicum activities especially for students. For this reason, a management that can manage an organization is more structured with a predetermined procedure. Management information system can assist laboratory management activities in the Department of Electrical Engineering. This laboratory management information system application is web based with PHP programming language. This web-based laboratory management information system is divided into two applications, back-end and front-end. The back-end application functions specifically to carry out laboratory management according to the access rights of the user, the data will be stored in a MySQL database. Stored data will be published on the front-end application.